Efficacy and safety of the initial hypotensive treatment with an optimized latanoprost composition - S. Yu. Petrov; E. V. Yani; A. N. Zhuravleva; O. M. Filippova; O. M. Kalinina; L. V. Yakubova; S. M. Kosakyan; L. V. Vasilenkova; I. V. Manukyan (Российский офтальмологический журнал)
Purpose: a comparative study of the efficacy and safety of Latanoprost-Optic, a new composition of excipients and the original latanoprost, in the initial therapy of primary open-angle glaucoma (POAG)Material and methods. We performed a prospective, randomized, comparative study of 60 previously untreated patients (71 eyes) with early and advanced POAG stages. During the screening visit, patients were randomly divided into the main (Latanoprost-Optic) and the control (original latanoprost) groups. The target points included intraocular pressure (IOP), visual acuity, MD and PSD perimetry indices, RNFL thickness, MRW, NFL, GCL, IPL, tear film break time, OSDI, and adverse events. The observation period was 12 weeks. IOP was measured 4 and 12 weeks from observation start.Results. The average decrease in IOP in the study group by the end of the observation was 32% and did not show any statistically significant differences from the original drug at any control point. A positive unreliable dynamic of the values of most functional parameters was noted, which may indicate the presence of an indirect neuroprotective effect. In the study group, there was a positive trend in tear film rupture time and OSDI. According to corneal confocal microscopy, no negative changes in dynamics were noted, in contrast to the control group. Reversible discomfort and mild redness of the bulbar conjunctiva were recorded in both groups. No serious or systemic adverse events were noted.Conclusion. Latanoprost-Optic has a hypotensive efficacy, comparable to the original latanoprost, and a high favorable safety profile.